Framing seascape connectivity modeling to prioritize marine conservation effort in China’s coastal sea - Kang, Yiyang; Lin, Yuxuan; Chen, Zhixue; Zhang, Xinyi; Li, Yi (Frontiers in Marine Science, 2024)
Anthropogenic disturbances and climate change are projected to become leading drivers of biodiversity loss and ecological connectivity degradation in marine ecosystems. However, the lack of quantitative understanding for seascape connectivity modeling hinders our ability in providing large-scale marine conservation guidance. By applying well-established theories and tools in landscape connectivity study and marine-specific indicators, we proposed a framework to evaluate the resistance-based seascape connectivity among marine habitats and Marine Protected Areas (MPAs) across China's coastal sea. The spatial vulnerability of marine habitats was further assessed to prioritize conservation effort. Our results showed that 82% of China's coastal seas were covered with middle to high level of resistance for migratory marine species, mainly due to concentrated inshore anthropogenic disturbances such as ship traffic and ocean pollution. With the modeled migration distances of different species guilds from short-range (25 km) to long-range (100 km), the area percentage of connected corridors increased from 12.02% to 44.68% in the study area. Vulnerable areas were identified as high resistance (high exposure) and abundant threatened species (high sensitivity) but with small number of connected corridors (low adaptive capacity), primarily distributed in offshore regions of Yellow Sea and East China Sea. Collectively, inshore regions with high anthropogenic disturbances warrant regulation and mitigation in major coastal cities and ports. While the lack of interconnected networks for offshore regions prioritized efforts to enhance seascape connectivity through the establishment of MPAs network. Sensitive species groups require more attention in future marine conservation, including threatened populations, climate refugees of marine species, and species with limited movement range. This study highlights the potential of developing seascape connectivity model based on landscape theories, and the importance of seascape connectivity study in guiding evidence-based marine conservation strategies.